Effect of Chlorhexidine on Micro-Shear Bond Strength of Two Adhesive Systems After Aging - Haleh Heshmat; Mohammad Hossein Jahangiri; Maryam Hoorizad Ganjkar; Mansoureh Emami Arjomand; Mohammad Javad Kharazifard (Islamic Dental Association of Iran, 2018)
Background and Aim: Recurrent caries and low bond strength are the main causes of composite restorations failure. This study sought to assess the effect of chlorhexidine (CHX) on micro-shear bond strength (MSBS) to dentin of a fourth generation adhesive system and a universal bonding agent after aging. Materials and Methods: This in vitro study used 32 extracted third molars and 3-5mm thick dentin slices were cut out of each tooth. Specimens were randomly divided into 8 groups. After etching, Scotchbond fourth generation bonding agent or Single Bond universal adhesive was applied on dentin surfaces and Z250 composite cylinders were bonded to the surfaces. In groups B, D, F and H, CHX was applied for 1 minute after etching and prior to the application of bonding agent. The MSBS was measured after 24 hours and four months of water storage at 37C using a micro-tensile tester. The collected data were analyzed using three-way ANOVA. Results: The Scotchbond yielded significantly higher MSBS than the universal adhesive at 24 hours and four months (P<0.001). Application of CHX significantly increased the MSBS of both adhesives to dentin at 24 hours and four months (P<0.001). The bond strength decreased over the time irrespective of the type of bonding system (P<0.001). Conclusion: The MSBS of Scotchbond fourth generation bonding agent was generally higher than that of Single Bond universal adhesive. The MSBS of both adhesives decreased over time, however, the application of CHX decelerated the deterioration rate.